Serological Detection of Toxoplasma Gondii in Animals and Human in Baghdad Province, Iraq - Shatti, Ali A. (Journal La Lifesci, 2024)
This study aims to investigate the prevalence of Toxoplasma gondii in field animals (cattle and sheep) and their owners at various areas in Baghdad province (Iraq) during September (2023) and February (2024). Also, it aims to identify the role of cat in transmission of infection to humans and animals. A total of 222 venous blood samples including 84 humans and 138 animals were collected under aseptic conditions into free-anticoagulant glass tubes. In addition, a total of 112 fecal cat samples were collected from different areas in Baghdad city into plastic containers to be examined by the flotation method. The results showed that 84 blood samples from animal owners detected the infection rate were 36.90%. In addition, there is a relationship between infection and age. The study shows that the highest age for infection is 26-30 years, and the percentage was 66.66%. also, the study included examining 138 blood samples from animals divided into 68 sheep and 70 cows’ infection parasite rate was also 41.30%, and through examining the collection of 120 samples of soil from different areas in the city of Baghdad, the percentage of infection with T. gondii parasite reached 32.50%, addition to the infection rate in cats was 50% by examining 112 stool samples collected from different areas in the same city. This study reported the increasing seroprevalence of T. gondii using different samples. The reason for this increase may be due to poor health conditions, the large number of stray cats, the accumulation of dirt, the low degree of health education, and ignorance of the sources of infection for the disease and the attempt to avoid them, as it was noted through the study that a large number of women raise cats in their homes. They do not know that cats are the source of the disease.